(untitled) (Journal of Engineering, 2005)
Most of the structures subjected to load tests had successfully passed it, although some of them had failed in cube and core tests. It is believed that membrane action may be the most important factor that made them do so. In the present study, an attempt is made to study the effect of membrane action on load test results. In this study, two space (3-D) model frames, nine panels (3×3), [consisted of rafts, columns, beams and slabs] were prepared for load test. The results show the positive role of the membrane action especially with camber beams and slabs in successful passing of the load test. Also there is enhancement in the deflection behavior of camber members compared with straight members.